Comparative Study in Enhancing AES Algorithm: Data Encryption - Jamal Khudair; Khanapi Abd Ghan; Mohd Rizuan Bin Baharon (Wasit Journal for Pure Sciences, 2023)
Abstract: Advanced Encryption Standard (AES) algorithm is defined as the standard algorithm for the encryption of transmitted data packets specially over cloud computing. Therefore, this review was conducted with the aim of studying its enhancing trials based on different methodologies. eleven published review articles were reviewed, these articles have compared encryption standards with respect to certain transmission parameters. The results have clearly concluded that the transmission of  data packets  over the Internet is considered as a major threat, especially when we talk about the evolution of computation power and quantum computers near epoch, therefore, new solutions have been developed to maintain  the issue of authentication and protect data by simultaneous encryption procedures. In addition, the comparative study concludes that enhancing AES algorithm is a promising field for data encryption. The study aims to provide academics with a better awareness of new encryption methods to enhance the performance of data encryption algorithms.